The German apprenticeship system - Wolfgang Franz; David W. Soskice (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1994)
This paper deals with the German apprenticeship training system. We first set the scene by describing the operation of the system, including the statistical picture in terms of supply and demand and costs; the relationship between the vocational training and the educational systems; the complex of regulations which companies engaging in apprenticeship training have to respect; and the relevant institutions. We then focus on the question why many companies make substantial net investments in marketable skills. Two simple ideas are developed as at least partial and complementary explanations of company' behaviour. The first is that it is significantly more expensive to teach company - specific skills to externally hired workers with marketable skills. The second idea tries to capture the belief that companies have that the apprenticeship system is some sort of competiton which companies have to go in for if they are to receive the best school leavers.
Keywords: 330; Betriebliche Ausbildung; Personalentwicklung; Bildungsinvestition; Deutschland; Theorie